Itogi vystupleniya sbornykh komand Rossii po sinkhronnomu plavaniyu v 2001 g. - Bugaets, I. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Detailed analysis of the performances of the elite and junior athletes of the Russion teams in synchronized swimming in 2001. With some statistics.